2018
DOI: 10.1021/acs.langmuir.8b02015
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of Trehalose for Cell Banking

Abstract: Advances in stem cell technology and regenerative medicine have underscored the need for effective banking of living cells. Cryopreservation, using very low temperatures to achieve suspended animation, is widely used to store or bank cells for later use. This process requires the use of cryoprotective agents (CPAs) to protect cells against damage caused by the cooling and warming process. However, current popular CPAs like DMSO can be toxic to cells and must be thoroughly removed from cells before they can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 77 publications
1
102
0
Order By: Relevance
“…Images indicate that the internalized FITC nanoparticle could be localized to the cytoplasm of the cells, but not the nucleus. For its cryoprotective activity, trehalose does not have to be confined to a specific subcellular location, [ 53 ] confirming that the observed uptake results of FITC‐nano by NK cells are indicative of potential biological relevance. Nuclear staining of NK cells revealed that the nanoparticles were localized to the cytoplasm of the cell (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Images indicate that the internalized FITC nanoparticle could be localized to the cytoplasm of the cells, but not the nucleus. For its cryoprotective activity, trehalose does not have to be confined to a specific subcellular location, [ 53 ] confirming that the observed uptake results of FITC‐nano by NK cells are indicative of potential biological relevance. Nuclear staining of NK cells revealed that the nanoparticles were localized to the cytoplasm of the cell (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 54%
“…Encapsulating trehalose inside CS:TPP nanoparticles enables it to be shuttled across the NK cell membrane, allowing for its intracellular presence where it can induce cryoprotection. [ 53 ] To identify the maximum amount of trehalose that can be encapsulated inside the CS:TPP nanoparticles, various concentrations of trehalose ranging from 1 to 20 mg mL −1 were directly dissolved in the TPP solution. Using a CS:TPP ratio of 3:1 and corresponding pH of 5.0 for chitosan and 9.5 for TPP, different concentrations of trehalose/TPP solution were added into the chitosan solution drop wise to assemble the encapsulated nanoparticle (trehalose‐loaded nanoparticle, nTre).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have reported efficient delivery of trehalose into cells using nanomaterials. The nanoparticles generally utilize the natural process of endocytosis to specifically deliver trehalose into cells without any harmful effects [29]. The use of nanoparticles for trehalose delivery and cryopreservation of cells with trehalose as sole CPA has been reported to maintain cell viability and functions.…”
Section: Chemical Delivery Methodsmentioning
confidence: 99%
“…In order to avoid the toxicity of organic solvents, several advanced biotechnology tools have been used to deliver trehalose into cells to provide both intracellular and extracellular cryopreservation. These techniques help to achieve organic solvent-free cell cryopreservation and high post-thaw cell survival efficiency [29]. These biotechnology tools, including both physical and chemical methods, can increase cellular membrane permeability and thus transport non-permeable trehalose into cells (Table 1).…”
Section: Trehalose Deliverymentioning
confidence: 99%